2016
DOI: 10.1080/20477724.2015.1133033
|View full text |Cite
|
Sign up to set email alerts
|

Primaquine treatment and relapse inPlasmodium vivaxmalaria

Abstract: The relapsing peculiarity of Plasmodium vivax is one of the prime reasons for sustained global malaria transmission. Global containment of P. vivax is more challenging and crucial compared to other species for achieving total malaria control/elimination. Primaquine (PQ) failure and P. vivax relapse is a major global public health concern. Identification and characterization of different relapse strains of P. vivax prevalent across the globe should be one of the thrust areas in malaria research. Despite renewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 77 publications
(100 reference statements)
1
37
0
Order By: Relevance
“…In this study, we did not find the other DENV-1 genotype (Genotype IV) known to circulate in Bali in 2010 [38] and other cities in Indonesia as well as in imported cases to other countries. The absence of Genotype IV in Bali together with genotype replacement is similar to that seen with the Jambi dengue outbreak [30], and other cities of Indonesia [18,29]. Altogether, our data suggest the ongoing replacement of DENV-1 Genotype IV by Genotype I in Bali.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we did not find the other DENV-1 genotype (Genotype IV) known to circulate in Bali in 2010 [38] and other cities in Indonesia as well as in imported cases to other countries. The absence of Genotype IV in Bali together with genotype replacement is similar to that seen with the Jambi dengue outbreak [30], and other cities of Indonesia [18,29]. Altogether, our data suggest the ongoing replacement of DENV-1 Genotype IV by Genotype I in Bali.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we investigated barriers to bed net use among IDPs in a region with ongoing human insecurity. Despite a high burden of malaria and free distribution of bed nets, only 29% of IDP households owned a bed net, compared to 16–75% in other studies in IDP camps in Eastern DRC and 8–90% in community-based surveys and surveillance data from sub-Saharan Africa [ 9 , 11 , 13 , 14 , 35 ]. In our survey of an IDP camp in Eastern DRC, 20% of individuals slept under a bed net the previous night, compared to 16–25% in another IDP camp [ 9 ] and 6–70% in other African studies [ 36 ].…”
Section: Discussionmentioning
confidence: 87%
“…The incidence of malaria in the DRC is estimated to be over 6 million cases annually, and malaria is the leading cause of childhood mortality in the country. We and others have previously reported that the burden of malaria is disproportionately high in Congolese IDP camps, and that bed nets are under-utilized [ 9 , 13 , 14 ]. The purpose of this study was to explore the factors influencing bed net ownership and use in an IDP camp with universal free bed net distribution using mixed qualitative and quantitative methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, many malaria endemic countries have not mandated routine glucose-6-phosphate dehydrogenase (G6PD) testing before initiating PQ for radical cure of patients infected by P. vivax malaria. This has led to the absence of PQ prescription or inconsiderate prescription and administration of PQ to P. vivax patients without being concerned about patients’ G6PD status and associated complications [ 31 ]. Indeed, the single greatest obstacle to PQ prescription is the rational fear of complications associated with this drug in G6PD deficient patients.…”
Section: Discussionmentioning
confidence: 99%